Information Security Construction of SPOC: Path Selection for Japanese Information Acquisition - Chen, Lei (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: In the traditional oral Japanese teaching model, Japanese courses emphasize theoretical knowledge of vocabulary and grammar, with few practical functions, low student interest in learning, and low attendance in class. They have made breakthroughs in information technology, e-commerce, and other professional fields. METHODS: A traditional teaching format is used, with the mains taught by teachers, without using learning platforms or offline teaching. Each lesson contains three elements: preschool, instructional practices, and external extensions. A cloud-based classroom learning platform is part of Cyber Chemistry’s preschool and out-of-school learning. Classroom instruction consisted primarily of discussions and exchanges between teachers and students, competitive exercises, and visualization of the results of conversations. To test the effectiveness of the SPOC-based model, the authors administered two speaking tests, as well as related questionnaires and interviews, during and at the end of the test. RESULTS: Improvements in the intermediate pretest and post-test speaking tests compared to the control group suggest that the Japanese hybrid speaking test model, SPOC, is positively compelling. CONCLUSION: The class stimulates students’ interest and motivation. It plays an active role in developing good learning practices and improving the learning of spoken Japanese.